Implementasi Penguatan Profil Pelajar Pancasila melalui Project Based Learning untuk Anak Usia Dini - Asya Ainul Fitri; Lilif Muallifatul Khorida Filasofa; Agus Sutiyono (Institut Agama Islam Negeri Madura, 2024)
Abstract This research aims to assess the effectiveness of strengthening the Pancasila Student Profile through project-based learning in early childhood education. The Pancasila Student Profile, which is an integral part of the independent curriculum, plays a central role in shaping the character of graduates by cultivating qualities such as faith, piety, morals, independence, cooperation and collaboration, global awareness, creativity and critical reasoning. When the research was carried out from September 4 to October 3 2023 at the Al Azhar 29 Islamic Kindergarten, Semarang, this research involved 17 children as participants using descriptive qualitative research methods. Data collection was carried out through observation, interviews and documentation. Research findings show that project-based learning significantly improves the character of Pancasila students at an early age by implementing a systematic approach through theme communication, project identification, project planning, preparing activity schedules, monitoring project progress, as well as assessing and evaluating project results. The theme used in the implementation of project learning in research is Aku Cinta Indonesia with the topic Nguri-nguri Central Java Culture-Market Snack Festival with the focus being Magelang City. Through project-based learning activities, children can stimulate their ability to collaborate, be independent, be creative, be tolerant and have noble character.